Trends in viral hepatitis liver-related morbidity and mortality in New South Wales, AustraliaResearch in context - Shane Tillakeratne; Sallie-Anne Pearson; Maryam Alavi; Behzad Hajarizadeh; Marianne Martinello; Matthew Law; Jacob George; Janaki Amin; Gail Matthews; Jason Grebely; Gregory J. Dore; Heather Valerio (Elsevier, 2024)
Summary: Background: Monitoring hepatitis B virus (HBV) and hepatitis C virus (HCV) liver-related morbidity and mortality is key to evaluate progress towards elimination targets. Methods: HBV and HCV notifications in NSW, Australia (1995-2022) were linked to hospital and mortality records. Temporal trends in decompensated cirrhosis (DC), hepatocellular carcinoma (HCC), and mortality were evaluated among people notified for HBV and HCV. Segmented Poisson regression models were used to assess the impact of the viral hepatitis elimination era (1 January 2015-31 December 2022) on advanced liver disease and mortality. Findings: During 1995-2022, there were 64,865 people with an HBV notification and 112,277 people with an HCV notification in NSW. Between 2002 and 2022, there were significant reductions in age-adjusted HBV- and HCV-related DC, HCC, and liver-related mortality. Among those with HBV, age-standardised incidence per 1000 person-years (py) in 2002, 2015, and 2022 was 3.08, 1.47, and 1.16 for DC (p < 0.001); 2.97, 1.45, and 0.75 for HCC (p < 0.001); and 2.84, 1.93, and 1.40 for liver-related mortality (p < 0.001). Among those with HCV, age-standardised incidence per 1000 py in 2002, 2015, and 2022, was 5.53, 4.57, and 2.31 for DC (p < 0.001); 2.22, 2.59, and 1.87 for HCC (p < 0.001); and 3.89, 4.73, and 3.16 for liver-related mortality (p < 0.001). In 2022, absolute liver-related mortality per 100,000 population was 0.95 for HBV and 3.56 for HCV. In adjusted analyses, older age, comorbidity, and a history of alcohol use disorder were associated with increased liver-related mortality among those with HBV and HCV. Interpretation: This population-level study demonstrated declining risks of DC, HCC, and mortality, with HBV-related declines commencing well before elimination era while HCV-related declines were mostly during elimination era. Population liver mortality indicates elimination target achieved for combined viral hepatitis and HBV, but not HCV. Funding: The Kirby Institute, UNSW Sydney, and New South Wales Ministry of Health, Australia.